Analgesia and sedation induced by Mucuna prurita seeds in rats - Ratnasoonya, W.D.; Lokupitiya, E.Y.K.; Dharmasiri, M.G. (My University, 1999)
In Sri Lankan folk medicine, seeds of Mucuna prurita (Hook) (Family: Leguminosae) are recommended to be consumed as a curry ingredient to relieve aches and pains. The seeds contain large quantities of dopa and nicotine. Thus it is possible that they have antinociceptive and perhaps also sedative activities. The aim of this study was to investigate these possibilities. A powdered seed suspension (PSS) of the seeds was made in 1% methyl cellulose. Different doses (750, 1,500 or 3,000 mg/kg) or vehicle were administered orally to male rats and the mid dose to female rats. 3 h later, analgesic potential (using hot plate and tail flick tests) and sedative potential (only with mid dose, and male rats, using the rat hole-board technique) were determined. A l l three doses were well tolerated and significantly {P < 0.05) increased both the reaction time and % maximum possible effect in hot plate test, indicating potent antinociception mediated supraspinally. In contrast, no analgesic activity was evident in the tail flick test. These effects were dose-reiated and not blocked by naloxone, an opioid receptor blocker. The mid dose caused only mild sedation. Further, in the females, the mid dose exhibited potent analgesia, as in males. This was not affected by the stage of the oestrous cycle. In addition, the treatment did not alter intestinal transit, muscle strength (as judged by a bar holding test) or muscle co-ordination (evaluated by bridge test). We conclude that antinociception of M. prurita seeds is not mediated by the opioid mechanism but possibly via dopamine and nicotine.